HOW TO DESIGN A WEB SURVEY USING SPRING BOOT WITH MYSQL: A ROMANIAN NETWORK CASE STUDY - Bucea-Manea-Țoniș, Radu; Tonis (Bucea-Manea), Rocsana (Annals of Spiru Haret University. Economic Series, 2017)
The article presents a survey applied on a representative sample of Romanian SMEs. The article represents a case study and focus on technical elements that allow collecting data from Romanian SMEs managers and save it in a MySql database. The Back-End component is developed with the newest Spring Boot MVC.